Perlindungan Hukum Terhadap Pencipta atas Pembajakan Buku Elektronik (E-Book) Yang di Sebarluaskan Secara Bebas Melalui Website - Pramesti Agustiani, Arda; Nur, Hilman; Mulyana, Aji (Indonesian Journal Publisher, 2025)
This study aims to analyse copyright and legal protection of copyrighted works of Electronic Books (E-Books) based on Law Number 28 of 2014 concerning Copyright. Copyright is an exclusive right granted by the state to the creator of the results of innovations that have economic and moral value, especially when realised in real form. This research uses a normative juridical method with a statutory approach to examine relevant legal provisions. The results show that Article 40 Paragraph (1) letter n of the Copyright Law implicitly recognises E-Books as adaptation works, namely the transfer of the form of a work into another format. As an adaptation work, E-Books get legal protection which includes preventive and repressive protection. Preventive protection aims to prevent copyright infringement through education and socialisation, while repressive protection is carried out through legal mechanisms if the creator's rights are violated. In conclusion, legal protection of E-Books is important to ensure that creators' rights are respected, both economically and morally. The government is expected to actively provide education on the importance of copyright and increase access to commercial courts in all regions to support law enforcement in the growing digital era.